Development of Strategies to Improve the Accuracy of Cost Estimates in Risk-Based Building Construction Projects - Astuti, Agnes Sari Diah; Isvara, Wisnu (Journal Research of Social Science, Economics, and Management, 2025)
The cost planning process is the initial stage of a construction project to plan for implementation costs that allow the project owner to determine economic feasibility and evaluate alternatives to achieve the desired feasibility. Poor planning can result in cost overruns, delays and even project cancellations. The cost planning process must be carried out accurately by considering many risk factors so that it can reduce the occurrence of cost overruns at the end of the project. Systemic risk is one of the factors that is often the main driver of the accuracy of cost estimates, especially during the early stages of project determination (AACE, 2020). The purpose of the study was to determine the most dominant systemic risk factors for the accuracy of cost estimates based on the owner's point of view. The methods used are qualitative and quantitative approaches or combined data from both (Ahnyar, Andriani, & Sukmana, 2020), surveys, expert validation, Risk Analysis using the Probability Impact Matrix and Forum Group Discussion (FGD). Questionnaire surveys were conducted on 34 respondents and processed with SPSS software to analyze the data. 13 systemic risk factors that affect the accuracy of the estimate were identified. The control strategy for the 13 recommended systemic risk factors is to develop operational standards for risk-based estimation, create a unit price database based on the realization price of previous projects, conduct training by involving competent senior estimates, add reserve or contingency factors, and look for alternative materials without reducing benefits and usefulness.